Trafficking of Eritreans in Egypt: facts and misconceptions - Daoud, Emad Guihad (AUC Knowledge Fountain, 2015)
The Egyptian government has not been able to effectively tackle the problem of trafficking of Eritreans and ensure that this crime would stop. Egypt continues to resist that Eritreans who are identified in the Sinai Peninsula are in most of the cases victims of trafficking. The Egyptian legal and institutional frameworks established have focused mainly on few forms of trafficking, neglecting the problem of Eritreans in the Sinai and framing it as a problem of illegal migration. In this thesis, the efforts carried out in Egypt to address the trafficking of Eritreans are analyzed carefully to highlight where the gaps that require bridging are. One of the reasons having a direct impact on the Egyptian inability to address the problem is the many gaps in the international legal framework addressing human trafficking. These gaps include failure to focus on the root causes that lead to trafficking, inadequate protection provided to the victims, lack of necessary international cooperation, tightened border measures, and low conviction rates for trafficking perpetrators. Egypt is recommended to amend its anti-trafficking law, ensure more effective coordination between the stakeholders involved in addressing trafficking, focus on capacity building of its police force and border-patrol in the Sinai, gear its diplomatic efforts towards international cooperation in this field, and work on eliminating the root causes of the crime by empowering the tribes of the Sinai. The thesis has reviewed primary and secondary literature and gathered a clear picture of trafficking in the Sinai through several interviews conducted with policy-makers and officials from international organizations involved in addressing trafficking of Eritreans in Egypt.